EFEKTIVITAS PROGRAM KELUARGA HARAPAN (PKH) DALAM PEMERATAAN KESEJAHTERAAN SOSIAL DI KELURAHAN BUNGO TAMAN AGUNG KECAMATAN BATHIN III KABUPATEN BUNGO - Fajar Ifan Dolly; Ade Sofa; Bella Sakila (Jurnal STIA Bengkulu, 2024)
Program Keluarga Harapan (PKH) is a program issued by the Ministry of Social Affairs in the short term the aim of this program was to reduce the Rumah Tangga Sangat Miskin (RTSM) and in the long term can stop the chain of poverty between generations to get out of the existing poverty problem. The aims of this study was to determine the effectiveness of Program Keluarga Harapan (PKH) in equalizing social welfare in Bungo Taman Agung Village, Bathin III District, Bungo Regency. In this study the authors used a descriptive method with a qualitative approach. The population of this research was KPM PKH Bungo Taman Agung Village and all Bungo Taman Agung Village officials with a sample of 15 people and using Purposive Sampling technique. The data sources in this study used primary data and secondary data. Data analysis techniques were data collection, data reduction, data presentation and conclusion drawing. The results showed that the effectiveness of the Family Hope Program (PKH) in equalizing social welfare in Bungo Taman Agung Village, Bathin III District, Bungo Regency was not effective, this could be seen from the understanding of the program which was not maximized cloud PKH Facilitator so that the lack of understanding of the program for Beneficiary Families (KPM), on target were are still KPM PKH who receive assistance but should be said to be prosperous, on time in the disbursement of funds which made the needs of KPM PKH delayed, the achievement of this goal improved the standard of living of KPM PKH through access to services and real changes felt by KPM towards complementary assistance. Of the five indicators, there were three indicators, namely understanding the program, right on target and on time that have not been effective and for the Government to be more selective in checking data and for the disbursement of PKH funds to be carried out on time.